Designing Strategy of Indonesia Port Car Terminal Based on Analysis of Profitability Ratio Before And After the IPO - Ilman, Hanif Insan; Chumaidiyah, Endang; Zulbetti, Rita (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2021)
Indonesia has managed to get out of the low-income zone and into the middle-income zone. However, Indonesia still has a challenge that is to get out of the middle-income trap zone. These challenges must be resolved by improving the performance of BUMN. Indonesia Port Center Terminal is one of the BUMN subsidiary companies precisely a subsidiary of Indonesia Port Center II (Persero). The purpose of the study was to determine differences in performance indicators before and after the IPO in profitability ratios, namely ROA, ROE, OPM, and NPM and recommendations for performance improvement strategies. The data obtained is based on the 2016-2019 financial statements and questionnaires to expert judgment. The method used is the Wilcoxon Paired t-Test, AHP, and SWOT test. The results of the Wilcoxon Paired t-Test test before and after the IPO were no difference. The results of the company's SWOT analysis are in the position of quadrant I (strength and opportunities). The recommended strategy applied in this condition is to support an aggressive growth policy that prioritizes the strengths and opportunities of the company.